2020
DOI: 10.1007/s42729-020-00379-8
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Liquid Organic Fertilizer and Zeolite on Plant Available Water Content of Sand and Growth of Perennial Ryegrass (Lolium perenne)

Abstract: The use of high permeability soils with low plant available water content (PAWC) for cultivation of plants in the greenhouses, green roofs, and urban green spaces requires frequent irrigation, which leads to high water consumption. This paper presents an innovative method consisting of combined use of sustainably produced liquid organic fertilizer (LOF) extracted from landscape grass waste and clinoptilolite zeolite for improving PAWC of sand. The study included four substrates, namely sand (S), sand with 20% … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…With the increase in temperature, the remaining soil moisture and nutrients in the early growth stage can promote oilseed flax growth and development. Organic fertilizers also increase oilseed flax's use of deep soil water storage, reduce soil moisture stress, regulate oilseed flax's water consumption process, play a regulatory role in "adjusting water with fertilizer", create a suitable soil moisture environment for oilseed flax growth, and have been proven to have an effect on reducing water consumption [30]. In this study, although there was no difference in total water consumption between years under organic fertilizer treatment, there was a significant difference in stage water consumption.…”
Section: Effect Of Different Organic Fertilizers On Water Consumption...mentioning
confidence: 99%
“…With the increase in temperature, the remaining soil moisture and nutrients in the early growth stage can promote oilseed flax growth and development. Organic fertilizers also increase oilseed flax's use of deep soil water storage, reduce soil moisture stress, regulate oilseed flax's water consumption process, play a regulatory role in "adjusting water with fertilizer", create a suitable soil moisture environment for oilseed flax growth, and have been proven to have an effect on reducing water consumption [30]. In this study, although there was no difference in total water consumption between years under organic fertilizer treatment, there was a significant difference in stage water consumption.…”
Section: Effect Of Different Organic Fertilizers On Water Consumption...mentioning
confidence: 99%
“…Typically, nutrients are negatively charged ions and are attracted to positively charged ions, such as NH 4 + , potassium (K + ), calcium (Ca 2+ ), and magnesium (Mg 2+ ) [17]. The ability of the cultivation medium to adsorb the cations is known as cation exchange capacity (CEC) which could be manipulated through soil amendment, such as fertiliser application, to improve soil properties during low nutrient provision conditions [32]. In soilless agriculture, controlling the number of nutrients and pH in the cultivation medium is easily performed by regular monitoring via a portable conductivity meter and a pH meter [33,90].…”
Section: Chemical Propertiesmentioning
confidence: 99%
“…Several studies on superabsorbent polymer hydrogel as a planting medium demonstrated positive effects on plant growth performances and physiological traits, viz. improved turf index quality, colour, density, ground cover, fruits, and essential oil yield in sweet basil and lemon [78] without compromising their physiological traits [31][32][33]91].…”
Section: Plant Growth Performancesmentioning
confidence: 99%
See 1 more Smart Citation